IMPLEMENTATION OF KINARA-KINARI BATIK PATTERN ON CLOTH - Dyanningrum Pradhikta; Ni Wayan Surya Wardhani; Fatmawati Fatmawati; Romy Setiawan (Jurusan Sastra Indonesia, 2019)
Kinara-Kinari relief in Badut Temple was one of the ideas to create a batik pattern inspired by a culture remnant in Malang. Previous research had generated the design of Kinara-Kinari batik pattern. According to validators, the batik pattern had met both aesthetic and artistic principles without abandoning the standards of the relief itself. Result of this development was implemented on a piece of batik cloth targeted for both men and women.